ORGANIZATION OF SELF-EDUCATIONAL OF THE FUTURE SPECIALISTS IN PHYSICAL REHABILITATION - Beseda, Nataliya; Vorobjov, Oleksiy (Continuing Professional Education: Theory and Practice, 2019)
The article justifies the research actuality of studying the problem of self-education of the future specialists in physical rehabilitation in the process of doing «Massage and self-massage» course. The authors prove the actual need in upgrading the qualification level of highly professional specialists. Having generalized the essence of foreign and domestic researchers’ works, the authors cover the issue of «students’ individual work». As a result, individual work aims, objectives and kinds have been defined, and peculiarities of its organizing in the process of teaching future specialists in physical rehabilitation have been analyzed. The article also contains the list of topics proposed for self-education. The authors justify the importance of applying current interactive teaching methods, pointing out the project method effectiveness. It is also noted that major criteria of students’ individual work in the process of doing «Massage and self-massage» course is their level of building corresponding practical skills. The most important of them include the following: mastering the technique of giving basic and assisted massage, and also overall and local massage for individuals having various diseases and damages of supporting-motor apparatus, excitatory, cardiovascular, digestive, respiratory systems etc., doing self-massage of certain body parts etc.